Papal primacy: : Polarity and paradox of ecumenical unity - Iheanacho, Valentine (Stellenbosch theological journal, 2024)
The idea of the Church of Rome "as Mother of the churches" is central to Roman Catholic ecclesiology. It gained prominence from the time of Pope Nicholas I (858-67). Afterwards, it became customary to refer to the Church of Rome as "Omnium Ecclesiarum Magistra, mater et caput" " (Teacher of all the Churches, mother and head). Within that ecclesiological conception stands solidly the place of the papacy with its centripetal function as the principle and foundation of Catholic unity. Ironically, the same institution that functions as a magnetic centre of unity in the Catholic Church is perceived as a polarising force by other churches within the Christian oikumene. However, starting essentially from Pope John XIII, the papacy has ecumenically sought to extend its unifying role beyond the ecclesiological confines of the Church of Rome. It jettisoned its previous "ecumenism of return" policy and became more disposed towards ecumenical dialogue. Pope John Paul II called the bishop of Rome "the first servant of unity." He was convinced that the promotion of Christian unity is "… a specific duty of the Bishop of Rome as the Successor of the Apostle Peter" (John Paul II 1995: ##4). This research is poised to look at the ecumenical place of the papacy and its polarity within ecumenical conversations and in the general orbit of "Global Christianity" that embraces unity and diversity as its very essence.